Review of Doravirine Resistance Patterns Identified in Participants During Clinical Development. (15th December 2020) - Martin, Elizabeth Anne; Lai, Ming-Tain; Ngo, Winnie; Feng, Meizhen; Graham, Donald; Hazuda, Daria J.; Kumar, Sushma; Hwang, Carey; Sklar, Peter; Asante-Appiah, Ernest
Abstract : Background: Doravirine (DOR) is a novel non-nucleoside reverse transcriptase inhibitor (NNRTI) approved for the treatment of HIV-1 infection in patients with no known DOR resistance-associated mutations. DOR was rationally designed to address limitations associated with other approved NNRTIs, particularly resistance from common NNRTI resistance-associated mutants containing K103N, Y181C, or G190A reverse transcriptase substitutions. Setting: Data to date from both in vitro studies and clinical trials have been compiled to summarize the resistance profile of DOR. Methods: We analyzed data from in vitro studies and phase 2 and 3 trials to assess the emergence of resistance-associated mutations and their impact on efficacy among participants treated with DOR. Results: DOR exhibited a distinct resistance profile compared with efavirenz and rilpivirine in vitro and in vivo; mutant viruses that were resistant to DOR showed limited cross-resistance to efavirenz and rilpivirine. In clinical trials, the development of DOR resistance-associated substitutions in reverse transcriptase was uncommon. Conclusion: Overall, minimal cross-resistance across NNRTIs was observed for DOR and limited development of DOR-related resistance. These data should assist clinicians in further understanding the resistance profile of DOR, so appropriate treatment decisions can be made for their patients.